Protocol to rapidly screen CRISPR-Cas9 gene editing outcomes in a cell population by mutating eGFP to a blue or non-fluorescent phenotype - Danny Wilbie; Enrico Mastrobattista; Olivier Gerrit de Jong (STAR Protocols, 2025)
Summary: When designing genome editing therapy, it is crucial to measure outcomes of DNA damage repair. Here, we present a protocol to distinguish the outcome of targeted DNA damage repair from the bottom up, through a previously established readout of enhanced green fluorescent protein (eGFP) to blue fluorescent protein (BFP) mutations. We describe steps for producing eGFP-positive cells and differentiating between non-homologous end joining-induced gene knockout and homology-directed repair-induced-directed mutation in these cells. This protocol has potential for high-throughput and scalable assessment of gene editing techniques.For complete details on the use and execution of this protocol, please refer to Walther et al.1 and Wilbie et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.